Reminiscence therapy for older people suffering from loneliness, anxiety and depression: a review of the literature - Syed Elias, Sharifah Munirah; Neville, Christine; Scott, Theresa (2015)
Reminiscence therapy is generally used to treat mental health problems. Reminiscence therapy uses the recall of past events, feelings and thoughts to facilitate pleasure, quality of life or adaptation to present circumstances. Reminiscence therapy is believed to provide numerous benefits to older people, especially those with loneliness, anxiety and depression. The aim of this review was to explore the literature related to reminiscence therapy for older people with loneliness, anxiety and depression. This review considered all types of research design. The inclusion criteria were studies that included older people aged 60 years and over, and outcomes on loneliness, anxiety or depression. A literature search strategy involved published and grey literature. Twenty-four studies met the inclusion criteria. Five key themes were derived from the literature: integration of theories in reminiscence therapy, different classification of reminiscence therapy, factors that may influence reminiscence therapy, the effectiveness of reminiscence therapy and the integration of new elements in reminiscence therapy. Further research in this area is needed in terms of improvement of methodological quality such as rigorous control group and integration of new elements in reminiscence therapy